1) (2x^2+x-2)+(1+2x-2x^2)=? 2) (2x^2+x-2)-(1+2x-2x^2)=? 3) (1+2x-2x^2)-(2x^2+x-2)=? 4) (2m^2-m-1)-2m^2-m-1)=? 5)2m^2-m-1-(m^2-2m+m-1)=? 6) (n^3+2n^2-n +1)+(1-n^3)=? решите пожалуста

1

Ответы и объяснения

2013-03-02T21:54:58+04:00

1) (2x^2+x-2)+(1+2x-2x^2)=2x^2+x-2+1+2x-2x^2=3x-1 ; 3x-1=0 ; 3x=1 ; x=1/3

2) (2x^2+x-2)-(1+2x-2x^2)=2x^2+x-2-1-2x+2x^2=4x^2-x-3 ; 4x^2-x-3=0 ; D=1-4*4*(-3)=1+48=49 ; sqrtD=sqrt49=7 ; x1=(1-7)/(2*4)=-6/8=-3/4=-0.75 ; x2=(1+7)/8=8/8=1 ; (x+0.75)*(x-1)

3) (1+2x-2x^2)-(2x^2+x-2)=1+2x-2x^2-2x^2-x+2=3+x-4x^2 ; -4x^2+x+3=0; D=1-4*(-4)*3=1+48=49 ; sqrtD=sqrt49=7; x1=(-1-7)/(2*-(4))=-8/(-8)=1 ; x2=(-1+7)/(2*(-4))=6/(-8)=-(3/4)=-0.75 ;

                                                                                                                                                  (x+0.75)*(x-1)

4) (2m^2-m-1)-2m^2-m-1)=2m^2-m-1-2m^2+m+1=0